Factors Affecting Sericulture Groups Decision Making on Career Sustaining in The Queen Sirikit Regional Office of Sericulture3, Khon Kaen Province - Pakittawichit, Thananchakorn; Saiyasopon, Sukhumvit; Mankan, Wipat; Katekao, Wiporn; Naressenie, Kasemchart (Interdisciplinary Academic and Research Journal, 2023)
Background and Aims: The occupation of agriculture has been closely associated with the Thai people for a long time. The cultivation of mulberry and sericulture have become alternative professions for Thai farmers. However, the number of individuals engaged in this profession is decreasing daily. This is due to the impact of borderless communication, the emergence of a new era of trade, and environmental changes, all of which affect farmers' livelihoods. The objective of this research was to study 1) The situation of mulberry cultivation and sericulture in the responsibility area of the Mulberry Cultivation Promotion Office, Region 3, which includes Khon Kaen Province. 2) The adaptation of farmers to economic, social, political, and technological changes. 3)Factors influencing the career decisions of the group of farmers. Methodology: The research methodology used is a mixed-method approach, with a sample group consisting of members engaged in mulberry and sericulture cultivation in six provinces: Chaiyaphum, Kalasin, Roi Et, Maha Sarakham, Mukdahan, and Khon Kaen, totaling 361 individuals. The research tools used include questionnaires and group interviews. Statistical analysis methods used include averages, percentages, and multiple regression analysis. Results: The study found that most mulberry and sericulture farmers primarily rely on household labor and typically own less than five rai of land. Many face challenges related to water availability for mulberry cultivation, with some areas experiencing insufficient water for adequate mulberry growth. There is a willingness among these farmers to adopt technological advancements in production and product processing with the assistance of government knowledge transfer initiatives. They also work to reduce unnecessary costs and collaborate in market negotiations. Factors influencing career decisions include personality traits, knowledge, understanding, and perception of the profession, job stability in mulberry and sericulture cultivation, quality of life, production/system management, land area used for cultivation, increasing age of farmers, succession planning, and participation in farmer groups. Conclusion: Most mulberry and sericulture farmers are the main household laborers, have an area of no more than 5 rai/household, have problems with water and dryness, and try to adapt to technology and receive assistance from the government. Factors affecting the decision to maintain a career include personality traits, knowledge, job stability, quality of life, production system, growing area, age, occupational succession, and joining groups for market bargaining.